Preparation method and application of biochar supported bimetallic CuMnO2 heterogeneous Fenton-like catalyst

By using biochar-supported bimetallic CuMnO2 heterophasic Fenton catalyst in the water environment, the problem of low removal efficiency of tetracycline antibiotics in the prior art is solved, and efficient, low-cost and environmentally friendly degradation effects are achieved.

CN119746885AInactive Publication Date: 2025-04-04QINGDAO AGRI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411743305.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has low efficiency in removing tetracycline antibiotics in a water environment, and the commonly used advanced oxidation technology has problems such as high cost, complex operation and poor catalyst stability.

Method used

Biochar is prepared by heating alfalfa leaf powder under an inert gas environment, and manganese salt, copper salt and biochar are hydrothermal reactions with biochar to prepare CuMnO2/biochar composite material.

Benefits of technology

It improves the degradation efficiency of tetracycline antibiotics, reduces the preparation cost, simplifies the operation process, and improves the stability and recycling of the catalyst through the mediation of biochar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746885A_ABST
    Figure CN119746885A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material preparation and water treatment, and provides a preparation method and application of a biochar supported bimetallic CuMnO2 heterogeneous Fenton-like catalyst, and the preparation method comprises the following steps: in an inert gas environment, heating alfalfa leaf powder, and cooling to obtain biochar; manganese salt, copper salt, water and strong base are mixed, and a bimetallic solution is obtained; mixing the bimetallic solution with the charcoal to obtain dispersion liquid; the dispersion liquid is subjected to a hydrothermal reaction, and biochar-loaded bimetal mixed liquid is obtained; and adjusting the biochar-loaded bimetallic mixed solution to be neutral by using dilute nitric acid, and then drying to obtain the CuMnO2 / biochar composite material. Compared with pure CuMnO2, the catalyst prepared by the method has the advantages that the agglomeration of CuMnO2 particles can be reduced and the specific surface area is increased by introducing the charcoal; meanwhile, the forbidden band width of CuMnO2 can be reduced by introducing the biochar, and the degradation efficiency of pollutants is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation and water treatment, and in particular to a biochar-supported bimetallic CuMnO 2 Preparation method and application of heterogeneous Fenton-type catalyst. Background Art

[0002] In recent years, tetracycline antibiotics have been detected more and more frequently in the environment. Their high hydrophilicity and low volatility make them remarkably persistent in the water environment. Tetracycline antibiotics remaining in the water will destroy the balance of the aquatic ecosystem and pose a threat to human health through enrichment in the food chain. The removal methods of such antibiotics in the water environment can be summarized as follows: physical method, biological method and advanced oxidation method. Among them, the physical method is simple to operate and has low energy consumption, but the cost is relatively high; the biological method is natural and environmentally friendly, but for sewage containing multiple pollutants, it is difficult to achieve good results by biological methods alone; advanced oxidation technologies mainly include electrochemical oxidation technology, photocatalytic oxidation technology and Fenton oxidation technology. Compared with other advanced oxidation technologies, Fenton technology has high efficiency in oxidizing organic matter and is safe to operate. The H in its liquid phase 2 O 2 As an environmentally friendly oxidant, the decomposition product is only H 2 O and O 2 The heterogeneous photo-Fenton technology can introduce light energy into the heterogeneous Fenton system, and generate more active free radicals by reacting with the catalyst to enhance the catalytic effect. Common heterogeneous photo-Fenton catalysts include various iron oxides such as Fe 3 O 4 Under light conditions, Fe 3+ Photolyzed and reduced to Fe 2+ , Fe 2+ With H in the system 2 O 2 Reaction to produce ·OH to degrade antibiotics. 2+ In comparison, Cu + Activated H 2 O 2 The rate of generating OH is higher than that of Fe 2+ Activated H 2 O 2 The rate of generating OH is much faster, Cu 2+ H 2 O 2 Reduction to Cu + Fe 3+ H 2 O 2 Reduction to Fe 2+ Has a faster reaction rate. Cu +The adsorption effect of tetracycline is better than that of Cu 2+ Better, but Cu 2 O is easily oxidized to CuO in the air, which greatly affects the degradation efficiency of pollutants. Therefore, metallic manganese is introduced into copper oxide.

[0003] Copper-manganese bimetallic oxide has good photoelectric properties and chemical stability. Compared with Cu monometallic catalyst, copper-manganese bimetallic oxide has good photoelectric properties and chemical stability. 2+ and Mn 2+ The synergistic effect of the redox pair greatly increases the reaction rate. But at the same time, copper-manganese bimetallic has problems such as low specific surface area and easy agglomeration. Biochar prepared by pyrolysis of waste biomass has the advantages of low cost and eco-friendliness. Its raw material alfalfa leaves are widely distributed in Northeast my country and North China. The raw materials are easy to obtain and inexpensive, the preparation cost is low, the operation is simple, and no complex reaction conditions are required. It can mediate electron transfer and prevent copper-manganese bimetallic oxides from agglomerating. At the same time, it can increase the specific surface area of ​​copper-manganese bimetallic oxides, thereby promoting the degradation of organic pollutants by heterogeneous photo-Fenton reaction. Therefore, a biochar-loaded bimetallic CuMnO 2 It is necessary to prepare heterogeneous Fenton-type catalysts and apply them to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a biochar-supported bimetallic CuMnO 2 The invention discloses a preparation method of a heterogeneous Fenton-type catalyst and its application, so as to overcome the problems existing in the prior art. The catalytic material prepared by the method has a good degradation effect on wastewater containing antibiotics.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a biochar-supported bimetallic CuMnO 2 The preparation method of a heterogeneous Fenton-type catalyst comprises the following steps:

[0007] (1) In an inert gas environment, alfalfa leaf powder is heated and then cooled to obtain biochar;

[0008] (2) mixing a manganese salt, a copper salt, water and a strong base to obtain a bimetallic solution;

[0009] (3) mixing the bimetallic solution and the biochar to obtain a dispersion;

[0010] (4) subjecting the dispersion to a hydrothermal reaction to obtain a biochar-loaded bimetallic mixed liquid;

[0011] (5) The biochar-loaded bimetallic mixture is adjusted to neutral with dilute nitric acid and then dried to obtain CuMnO2 / biochar composites.

[0012] Preferably, the inert gas in step (1) is nitrogen;

[0013] The heating temperature in step (1) is 500-600° C., and the heating time in step (1) is 1-3 hours;

[0014] The cooling temperature in the step (1) is 20 to 30°C.

[0015] Preferably, the manganese salt in step (2) is one or more of manganese chloride, manganese sulfate and manganese nitrate;

[0016] The copper salt in step (2) is one or more of copper sulfate, copper chloride, copper nitrate and copper carbonate;

[0017] The strong base in step (2) is sodium hydroxide.

[0018] Preferably, in step (2), the atomic ratio of Mn to Cu in the manganese salt and the copper salt is 0.8-1.2:0.8-1.2;

[0019] In the step (2), the molar mass ratio of the copper salt to the strong base is 10-15 mmol: 3-5 g;

[0020] The molar volume ratio of the copper salt to water in the step (2) is 10-15 mmol:60-90 mL.

[0021] Preferably, the mass molar ratio of the biochar in step (3) to the copper salt in step (2) is 0-0.8 g:10-15 mmol.

[0022] Preferably, the temperature of the hydrothermal reaction in step (4) is 80 to 160° C., and the time of the hydrothermal reaction in step (4) is 12 to 24 hours.

[0023] Preferably, the concentration of dilute nitric acid in step (5) is 0.8-1.2 mmol / L.

[0024] Preferably, the drying temperature in step (5) is 60 to 80° C., and the drying time in step (5) is 6 to 8 hours.

[0025] The present invention also provides a biochar-supported bimetallic CuMnO 2 CuMnO obtained by the preparation method of heterogeneous Fenton-like catalyst 2 / biochar composites.

[0026] The present invention also provides a biochar-supported bimetallic CuMnO 2Application of heterogeneous Fenton-like catalysts in wastewater treatment.

[0027] The present invention has the following beneficial effects:

[0028] (1) The present invention uses alfalfa leaves as raw materials, which are widely distributed in Northeast my country and North China. The raw materials are easily available and inexpensive, the preparation cost is low, the operation is simple, and no complicated reaction conditions are required.

[0029] (2) The biochar prepared by the present invention is easy to centrally process, has low pollution, and can fix carbon when reapplied to the soil.

[0030] (3) The preparation method of the present invention is a hydrothermal method, which has a simple operation process and mild conditions; the photocatalytic degradation effect of pollutants is significant; the stability is good and the preparation cost is low; the hydrothermal method of the present invention can shorten the preparation time to twelve hours, which greatly improves the reaction rate and is suitable for industrial production and application.

[0031] (4) CuMnO obtained by the present invention 2 / Biochar composite material is a magnetic material. In the process of photocatalytic treatment of wastewater, it is very necessary to recover the catalyst after the reaction is completed to avoid secondary pollution of the water body. The composite material can be effectively recovered through an external magnet, which improves the recycling of the catalyst.

[0032] (5) The catalyst prepared by the method of the present invention and pure CuMnO 2 In comparison, the introduction of biochar can reduce the CuMnO 2 The agglomeration of particles increases the specific surface area; at the same time, the introduction of biochar can reduce the CuMnO 2 bandgap width; in addition, biochar can effectively promote the separation of photogenerated carriers, inhibit the recombination of photogenerated electrons and holes, and greatly improve the degradation efficiency of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The CuMnO of Example 1 2 Materials and Example 3 CuMnO 2 / SEM images of biochar composites;

[0034] Figure 2 XRD diffraction patterns of the materials obtained in Examples 1 to 5;

[0035] Figure 3 This is a diagram showing the degradation effect of the materials obtained in Examples 1 to 5 on chlortetracycline in chlortetracycline solution. DETAILED DESCRIPTION

[0036] The present invention provides a biochar-supported bimetallic CuMnO 2The preparation method of a heterogeneous Fenton-type catalyst is characterized by comprising the following steps:

[0037] (1) In an inert gas environment, alfalfa leaf powder is heated and then cooled to obtain biochar;

[0038] (2) mixing a manganese salt, a copper salt, water and a strong base to obtain a bimetallic solution;

[0039] (3) mixing the bimetallic solution and the biochar to obtain a dispersion;

[0040] (4) subjecting the dispersion to a hydrothermal reaction to obtain a biochar-loaded bimetallic mixed liquid;

[0041] (5) The biochar-loaded bimetallic mixture is adjusted to neutral with dilute nitric acid and then dried to obtain CuMnO 2 / biochar composites.

[0042] In the present invention, fresh alfalfa leaves are firstly picked, the stems are removed, the alfalfa leaves are washed and dried, and then ground to obtain alfalfa leaf powder.

[0043] In the present invention, the drying temperature is preferably 40 to 60°C, more preferably 42 to 58°C, and even more preferably 45 to 55°C.

[0044] In the present invention, the drying time is preferably 6 to 10 hours, more preferably 7 to 9 hours, and more preferably 7.5 to 8.5 hours.

[0045] In the present invention, the particle size of the alfalfa leaf powder is 50 to 100 μm, more preferably 60 to 90 μm, and even more preferably 70 to 80 μm.

[0046] In the present invention, the inert gas in step (1) is preferably nitrogen.

[0047] In the present invention, the heating temperature in step (1) is preferably 500-600°C, more preferably 520-580°C, and even more preferably 540-560°C.

[0048] In the present invention, the heating time in step (1) is preferably 1 to 3 hours, more preferably 1.2 to 2.8 hours, and even more preferably 1.5 to 2.5 hours.

[0049] In the present invention, the cooling temperature in step (1) is preferably 20 to 30°C, more preferably 22 to 28°C, and even more preferably 24 to 26°C.

[0050] In the present invention, the cooling is followed by grinding to obtain biochar.

[0051] In the present invention, the particle size of the biochar is preferably 5 to 20 μm, more preferably 7 to 18 μm, and even more preferably 10 to 15 μm.

[0052] In the present invention, manganese salt and copper salt are first dissolved in water and continuously stirred until they are evenly dispersed, and a strong base is added in the stirring state and the mixture is continuously mixed to obtain a bimetallic solution.

[0053] In the present invention, the manganese salt in step (2) is preferably one or more of manganese chloride, manganese sulfate and manganese nitrate.

[0054] In the present invention, the copper salt in step (2) is preferably one or more of copper sulfate, copper chloride, copper nitrate and copper carbonate.

[0055] In the present invention, the continuous stirring rate is preferably 200 to 500 rpm, more preferably 250 to 450 rpm, and even more preferably 300 to 400 rpm.

[0056] In the present invention, the strong base in step (2) is preferably sodium hydroxide.

[0057] In the present invention, the mixing time in step (2) is preferably 5 to 20 minutes, more preferably 7 to 18 minutes, and even more preferably 10 to 15 minutes.

[0058] In the present invention, the atomic ratio of Mn to Cu in the manganese salt and the copper salt in step (2) is preferably 0.8-1.2:0.8-1.2, more preferably 0.9-1.1:0.9-1.1, and more preferably 1:1.

[0059] In the present invention, the molar mass ratio of the copper salt to the strong base in step (2) is preferably 10-15 mmol:3-5 g, more preferably 11-14 mmol:3.5-5 g, and more preferably 12-13 mmol:3.5-4.5 g.

[0060] In the present invention, the molar volume ratio of the copper salt to water in step (2) is preferably 10-15 mmol:60-90 mL, more preferably 11-14 mmol:65-85 mL, and more preferably 12-13 mmol:70-80 mL.

[0061] In the present invention, the mass molar ratio of the biochar in step (3) to the copper salt in step (2) is preferably 0-0.8 g:10-15 mmol, more preferably 0.2-0.7 g:2.2-3.8 mmol, and more preferably 0.4-0.6 g:2.5-3.5 mmol.

[0062] In the present invention, the mixing time in step (3) is preferably 5 to 20 minutes, more preferably 7 to 18 minutes, and even more preferably 10 to 15 minutes.

[0063] In the present invention, the mixing rate is preferably 200 to 500 rpm, more preferably 250 to 450 rpm, and even more preferably 300 to 400 rpm.

[0064] In the present invention, the temperature of the hydrothermal reaction in step (4) is preferably 80 to 160°C, more preferably 90 to 150°C, and even more preferably 100 to 140°C.

[0065] In the present invention, the time of the hydrothermal reaction in step (4) is preferably 12 to 24 hours, more preferably 14 to 20 hours, and even more preferably 16 to 18 hours.

[0066] In the present invention, the concentration of the dilute nitric acid in step (5) is 0.8 to 1.2 mmol / L, more preferably 0.9 to 1.1 mmol / L, and more preferably 1.0 mmol / L.

[0067] In the present invention, the biochar-loaded bimetallic mixed solution is adjusted to neutral with dilute nitric acid, and then washed alternately with water and anhydrous ethanol to remove impurities, and then dried under vacuum. After drying, the CuMnO 2 / biochar composites.

[0068] In the present invention, the number of alternating washings with water and anhydrous ethanol is preferably 2 to 8 times, more preferably 3 to 7 times, and even more preferably 4 to 6 times.

[0069] In the present invention, the drying temperature in step (5) is preferably 60 to 80°C, more preferably 62 to 78°C, and even more preferably 65 to 75°C.

[0070] In the present invention, the drying time in step (5) is 6 to 8 hours, more preferably 6.2 to 7.8 hours, and more preferably 6.5 to 7.5 hours.

[0071] In the present invention, in step (5), CuMnO 2 The particle size of the carbon / biochar composite material is preferably 5 to 30 μm, more preferably 10 to 25 μm, and even more preferably 15 to 20 μm.

[0072] The present invention also provides a biochar-supported bimetallic CuMnO 2 CuMnO obtained by the preparation method of heterogeneous Fenton-like catalyst 2 / biochar composites.

[0073] The present invention also provides a biochar-supported bimetallic CuMnO 2 Application of heterogeneous Fenton-like catalysts in wastewater treatment.

[0074] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0075] Example 1

[0076] 12mmol manganese chloride and 12mmol copper nitrate were dissolved in 80mL water (wherein the atomic ratio of Mn to Cu in manganese chloride and copper nitrate was 1:1), and stirred continuously at a rate of 300rpm until uniformly dispersed. 4.4g sodium hydroxide was added under stirring, and mixing was continued for 10min until uniformly dispersed. The above solution was transferred to a reactor, and then hydrothermally reacted at 100°C for 12h, and then cooled to room temperature. The solution was adjusted to neutral with dilute nitric acid with a concentration of 1.0mmol / L, and then washed alternately with water and anhydrous ethanol for 3 times to remove impurities, and then dried at 70°C for 6h under vacuum. After drying, the CuMnO with a particle size of 15μm was obtained by grinding. 2 Material.

[0077] Example 2

[0078] Pick fresh alfalfa leaves, remove the stems, wash the alfalfa leaves, dry them at 50°C for 8 hours, and grind them to obtain alfalfa leaf powder with a particle size of 74 μm. Nitrogen is introduced into a tubular furnace, and the alfalfa leaf powder is placed in the tubular furnace, heated at 550°C for 2 hours, cooled to 25°C, and ground to obtain biochar with a particle size of 10 μm.

[0079] 12 mmol manganese chloride and 12 mmol copper nitrate were dissolved in 80 mL water (wherein the atomic ratio of Mn and Cu in manganese chloride and copper nitrate was 1:1), and the mixture was stirred continuously at a rate of 300 rpm until the metal salt was completely dissolved. Subsequently, 0.2 g biochar was added and stirred for 10 min until uniformly dispersed. Then, 4.4 g sodium hydroxide was added and stirred for 10 min at a rate of 300 rpm to obtain a dispersion. The above solution was transferred to a reactor, and then a hydrothermal reaction was carried out at 100 °C for 12 h, and then cooled to room temperature to obtain a biochar-loaded bimetallic mixed solution.

[0080] The biochar-loaded bimetallic mixture was adjusted to neutral with 1.0 mmol / L dilute nitric acid, and then washed with water and anhydrous ethanol for three times to remove impurities. Then, it was dried at 70 °C for 6 h in a vacuum environment. After drying, the CuMnO with a particle size of 15 μm was obtained by grinding. 2 / biochar composites.

[0081] Example 3

[0082] Pick fresh alfalfa leaves, remove the stems, wash the alfalfa leaves, dry them at 50°C for 8 hours, and grind them to obtain alfalfa leaf powder with a particle size of 74 μm. Nitrogen is introduced into a tubular furnace, and the alfalfa leaf powder is placed in the tubular furnace, heated at 550°C for 2 hours, cooled to 25°C, and ground to obtain biochar with a particle size of 10 μm.

[0083] 12 mmol manganese chloride and 12 mmol copper nitrate were dissolved in 80 mL water (wherein the atomic ratio of Mn and Cu in manganese chloride and copper nitrate was 1:1), and the mixture was stirred continuously at a rate of 300 rpm until the metal salt was completely dissolved. Subsequently, 0.4 g biochar was added and stirred for 10 min until uniformly dispersed. Then, 4.4 g sodium hydroxide was added and stirred for 10 min at a rate of 300 rpm to obtain a dispersion. The above solution was transferred to a reactor, and then a hydrothermal reaction was carried out at 100 °C for 12 h, and then cooled to room temperature to obtain a biochar-loaded bimetallic mixed solution.

[0084] The biochar-loaded bimetallic mixture was adjusted to neutral with 1.0 mmol / L dilute nitric acid, and then washed with water and anhydrous ethanol for three times to remove impurities. Then, it was dried at 70 °C for 6 h in a vacuum environment. After drying, the CuMnO with a particle size of 15 μm was obtained by grinding. 2 / biochar composites.

[0085] The CuMnO prepared in this example 2 / biochar composite material and CuMnO obtained in Example 1 2 The materials were observed by scanning electron microscopy, such as Figure 1 As shown (the above figure is CuMnO 2 Materials, the figure below is CuMnO 2 / biochar composites).

[0086] from Figure 1 CuMnO can be seen in 2 Compared with the original form of biochar, biochar dispersed in CuMnO 2 surface, which to some extent prevents CuFeO 2 The aggregation of particles, compared with the two single materials, CuMnO 2 / biochar composites can expose more active sites.

[0087] Example 4

[0088] Pick fresh alfalfa leaves, remove the stems, wash the alfalfa leaves, dry them at 50°C for 8 hours, and grind them to obtain alfalfa leaf powder with a particle size of 74 μm. Nitrogen is introduced into a tubular furnace, and the alfalfa leaf powder is placed in the tubular furnace, heated at 550°C for 2 hours, cooled to 25°C, and ground to obtain biochar with a particle size of 10 μm.

[0089] 12 mmol manganese chloride and 12 mmol copper nitrate were dissolved in 80 mL water (wherein the atomic ratio of Mn and Cu in manganese chloride and copper nitrate was 1:1), and the mixture was stirred continuously at a rate of 300 rpm until the metal salt was completely dissolved. Subsequently, 0.6 g biochar was added and stirred for 10 min until uniformly dispersed. Then, 4.4 g sodium hydroxide was added and stirred for 10 min at a rate of 300 rpm to obtain a dispersion. The above solution was transferred to a reactor, and then a hydrothermal reaction was carried out at 100 °C for 12 h, and then cooled to room temperature to obtain a biochar-loaded bimetallic mixed solution.

[0090] The biochar-loaded bimetallic mixture was adjusted to neutral with 1.0 mmol / L dilute nitric acid, and then washed with water and anhydrous ethanol for three times to remove impurities. Then, it was dried at 70 °C for 6 h in a vacuum environment. After drying, the CuMnO with a particle size of 15 μm was obtained by grinding. 2 / biochar composites.

[0091] Example 5

[0092] Pick fresh alfalfa leaves, remove the stems, wash the alfalfa leaves, dry them at 50°C for 8 hours, and grind them to obtain alfalfa leaf powder with a particle size of 74 μm. Nitrogen is introduced into a tubular furnace, and the alfalfa leaf powder is placed in the tubular furnace, heated at 550°C for 2 hours, cooled to 25°C, and ground to obtain biochar with a particle size of 10 μm.

[0093] 12 mmol manganese chloride and 12 mmol copper nitrate were dissolved in 80 mL water (wherein the atomic ratio of Mn and Cu in manganese chloride and copper nitrate was 1:1), and the mixture was stirred continuously at a rate of 300 rpm until the metal salt was completely dissolved. Subsequently, 0.8 g biochar was added and stirred for 10 min until uniformly dispersed. Then, 4.4 g sodium hydroxide was added and stirred for 10 min at a rate of 300 rpm to obtain a dispersion. The above solution was transferred to a reactor, and then a hydrothermal reaction was carried out at 100 °C for 12 h, and then cooled to room temperature to obtain a biochar-loaded bimetallic mixed liquid.

[0094] The biochar-loaded bimetallic mixture was adjusted to neutral with 1.0 mmol / L dilute nitric acid, and then washed with water and anhydrous ethanol for three times to remove impurities. Then, it was dried at 70 °C for 6 h in a vacuum environment. After drying, the CuMnO with a particle size of 15 μm was obtained by grinding. 2 / biochar composites.

[0095] Effect test:

[0096] The materials prepared in Examples 1 to 5 were tested by X-ray diffractometer. Figure 2 shown.

[0097] from Figure 2 It can be seen that the CuMnO prepared in Example 1 of the present application 2 The diffraction peaks are similar to those of typical CuMnO 2 phase (JCPDS No.50-0860). The addition of biochar has a good effect on CuMnO 2 The orientation and structure of CuMnO 2 The diffraction peak of CuMnO 2 CuMnO was found in both biochar and biochar composites. 2 and the characteristic diffraction peaks of biochar, which are similar to those of CuMnO 2 It is consistent with the dual-phase structure of biochar, and the composite material is relatively pure without producing a third phase.

[0098] The materials prepared in Examples 1 to 5 were prepared into 100 mg·L -1 CuMnO of 5 different biochar contents 2 / biochar composite material, and then added to a concentration of 35 mg·L -1 The degradation effects of materials with different biochar contents on chlortetracycline at different times were observed in the chlortetracycline solution. Figure 3 shown.

[0099] from Figure 3 It can be seen that the CuMnO prepared in Examples 2 to 4 2 The degradation rate of chlortetracycline by CuMnO / biochar composites was higher than that of pure CuMnO 2 , and when the content of biochar exceeds a certain value, the degradation rate decreases, which shows that within a certain range, CuMnO 2 There is a good synergistic effect with biochar.

[0100] From the above examples, it can be seen that the present invention provides a biochar-supported bimetallic CuMnO 2The preparation method and application of a heterogeneous Fenton-like catalyst include the following steps: heating alfalfa leaf powder and then cooling it in an inert gas environment to obtain biochar; mixing manganese salt, copper salt, water and a strong base to obtain a bimetallic solution; mixing the bimetallic solution and biochar to obtain a dispersion; subjecting the dispersion to a hydrothermal reaction to obtain a biochar-loaded bimetallic mixed solution; adjusting the biochar-loaded bimetallic mixed solution to neutrality with dilute nitric acid and then drying it to obtain CuMnO 2 / Biochar composite material. The present invention uses alfalfa leaves as raw materials, which are easily available and inexpensive, have low preparation costs, are simple to operate, and do not require complex reaction conditions. The biochar prepared by the present invention is easy to centrally process, has low pollution, and can also fix carbon when the biochar is re-applied to the soil. The preparation method of the present invention is a hydrothermal method, which has a simple operation process and mild conditions; the photocatalytic degradation of pollutants is significant; the stability is good and the preparation cost is low; the hydrothermal method of the present invention can shorten the preparation time to twelve hours, which greatly improves the reaction rate and is suitable for industrial production and application. The CuMnO obtained by the present invention 2 / Biochar composite material is a magnetic material. In the process of photocatalytic treatment of wastewater, it is very necessary to recover the catalyst after the reaction is completed to avoid secondary pollution to the water body. The composite material can be effectively recovered by an external magnet, which improves the recycling of the catalyst. The catalyst prepared by the method of the present invention is comparable to pure CuMnO 2 In comparison, the introduction of biochar can reduce the CuMnO 2 The agglomeration of particles increases the specific surface area; at the same time, the introduction of biochar can reduce the CuMnO 2 bandgap width; in addition, biochar can effectively promote the separation of photogenerated carriers, inhibit the recombination of photogenerated electrons and holes, and greatly improve the degradation efficiency of pollutants.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a biochar-supported bimetallic CuMnO2 heterogeneous Fenton-like catalyst, characterized in that: It includes the following steps: (1) In an inert gas environment, alfalfa leaf powder is heated and then cooled to obtain biochar; (2) mixing a manganese salt, a copper salt, water and a strong base to obtain a bimetallic solution; (3) mixing the bimetallic solution and the biochar to obtain a dispersion; (4) subjecting the dispersion to a hydrothermal reaction to obtain a biochar-loaded bimetallic mixed liquid; (5) The biochar-loaded bimetallic mixed solution is adjusted to neutral with dilute nitric acid and then dried to obtain a CuMnO2 / biochar composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the inert gas is nitrogen; The heating temperature in step (1) is 500-600° C., and the heating time in step (1) is 1-3 hours; The cooling temperature in the step (1) is 20 to 30°C.

3. The preparation method according to claim 1, characterized in that: In step (2), the manganese salt is one or more of manganese chloride, manganese sulfate and manganese nitrate; The copper salt in step (2) is one or more of copper sulfate, copper chloride, copper nitrate and copper carbonate; The strong base in step (2) is sodium hydroxide.

4. The preparation method according to claim 1, characterized in that: In the step (2), the atomic ratio of Mn to Cu in the manganese salt and the copper salt is 0.8-1.2:0.8-1.2; In the step (2), the molar mass ratio of the copper salt to the strong base is 10-15 mmol: 3-5 g; The molar volume ratio of the copper salt to water in the step (2) is 10-15 mmol:60-90 mL.

5. The preparation method according to claim 1, characterized in that: The mass molar ratio of the biochar in step (3) to the copper salt in step (2) is 0-0.8 g:10-15 mmol.

6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (4) is 80 to 160° C., and the time of the hydrothermal reaction in step (4) is 12 to 24 hours.

7. The preparation method according to claim 1, characterized in that: The concentration of dilute nitric acid in step (5) is 0.8-1.2 mmol / L.

8. The preparation method according to claim 1, characterized in that: The drying temperature in step (5) is 60 to 80° C., and the drying time in step (5) is 6 to 8 hours.

9. A CuMnO2 / biochar composite material obtained by the method for preparing a biochar-supported bimetallic CuMnO2 heterogeneous Fenton-like catalyst as described in any one of claims 1 to 8.

10. Use of a biochar-supported bimetallic CuMnO2 heterogeneous Fenton-like catalyst as claimed in claim 8 in treating sewage.

Citation Information

Patent Citations

  • Method for preparing delafossite structure CuFeO2 / biochar composite material

    CN111333117A

  • CuFeO2 / biochar composite magnetic material and preparation method thereof

    CN111389351A

  • Cellulose-based composite bead for activating peroxymonosulfate degradation dye and preparation method of cellulose-based composite bead

    CN117654641A

  • Environment-friendly water purification composite material g-C3N4 / CuMnO2 and preparation method thereof

    CN118663304A

  • Preparation method of biochar-loaded bimetallic MnFeO2 heterogeneous Fenton-like catalyst

    CN119215925A